Exploring Middle School Students' Mathematical Connection Skills in Solving Systems of Linear Equations - Mulya, Dita; Darwati, Jaenudin; Sarah Inayah (EDUPEDIA Publisher, 2024)
This study aims to analyze the ability of mathematical connections in solving concept problems between mathematics, mathematical concepts, and other studies, as well as the ability to connect mathematical concepts to solve problems in everyday life. This research method is descriptive qualitative. The subjects of this study were 36 students of class VIII SMP Negeri 1 Cipanas. The instruments used were test questions describing mathematical connections and interviews. The results of this study indicate that students who can connect concepts between Mathematics are 68% in the medium category, then for the ability to connect between Mathematical concepts with other studies is 63% in the medium category and for the ability to connect mathematical concepts to solve problems in everyday life. day is 81% with the High category. So it can be concluded that the percentage of mathematical connections at the VII grade junior high school level with SPLDV material is 70.6% in the high category.